2003
DOI: 10.1111/j.1574-6976.2003.tb00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of oritavancin and related glycopeptide antibiotics

Abstract: Oritavancin (LY333328) is a semisynthetic glycopeptide antibiotic having excellent bactericidal activity against glycopeptide-susceptible and -resistant Gram-positive bacteria. Oritavancin is the N-alkyl-p-chlorophenylbenzyl derivative of chloroeremomycin (LY264826) and is currently in phase III clinical trials for use in Gram-positive infections. Studies show that oritavancin and related alkyl glycopeptides inhibit bacterial cell wall formation by blocking the transglycosylation step in peptidoglycan biosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
161
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(168 citation statements)
references
References 133 publications
(323 reference statements)
3
161
0
4
Order By: Relevance
“…Thus, this inhibition of bacterial cell wall synthesis is not derived from inhibition of transpeptidase-catalyzed cross-linking derived from D-Ala-D-Ala/D-Ala-D-Lac binding but rather, likely arises from direct inhibition of transglycosylase by the peripherally modified disaccharide. Previous studies of Kahne and coworkers (32,33) and others (30,31,55) have shown such direct inhibition of transglycosylase by 5 and related CBP-bearing analogs. Finally, the potent pocket-modified vancomycin analog 8, containing the peripheral CBP modification, inhibits cell wall synthesis more effectively than 4, lacking the CBP modification and more potently than either 5 or 6, lacking a productive pocket modification.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, this inhibition of bacterial cell wall synthesis is not derived from inhibition of transpeptidase-catalyzed cross-linking derived from D-Ala-D-Ala/D-Ala-D-Lac binding but rather, likely arises from direct inhibition of transglycosylase by the peripherally modified disaccharide. Previous studies of Kahne and coworkers (32,33) and others (30,31,55) have shown such direct inhibition of transglycosylase by 5 and related CBP-bearing analogs. Finally, the potent pocket-modified vancomycin analog 8, containing the peripheral CBP modification, inhibits cell wall synthesis more effectively than 4, lacking the CBP modification and more potently than either 5 or 6, lacking a productive pocket modification.…”
Section: Resultsmentioning
confidence: 99%
“…Vancomycin inhibits late-stage peptidoglycan biosynthesis and acts outside the cytoplasmic membrane, which results in the intracellular accumulation of UDP-linked MurNAc-pentapeptide precursors (272,273). The vancomycin complex involves a number of hydrogen bonds between the peptide component of vancomycin and the D-Ala-D-Ala residue (5,15). Any process that interferes with vancomycin binding to D-Ala-D-Ala residues in the cell wall will decrease the potency of the drug.…”
Section: Mechanism Of Vancomycin Actionmentioning
confidence: 99%
“…The presence of antibiotic and other chemotherapeutic compounds becoming a relief thingeither nowadays or in the future, however it's still not enough yet. The main problem is there is a must for the presence of new medical agents which have a better potency in comparison to what have existed todays [2]. One of effort which can be done is doing a screening of bioactive compound towards any organisms or doing a modification towards the compounds which have existed todays.…”
Section: Introductionmentioning
confidence: 99%